(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objective of this study was to assess the serum ferritin level and quantitate ultrasound elastography as a marker to distinguish dogs with benign and malignant liver tumors. Materials and Methods: Twenty-eight dogs were determined the serum ferritin and ultrasound elastography by using fine-needle aspiration biopsy. Results: Our results demonstrated that dogs with malignant liver tumors had significantly higher mean serum ferritin concentrations than those with benign liver tumors (p = 0.004). The mean intensity of blue and red colors from elastography was greater in the malignant than those in the benign group, especially for the blue color, meaning that lesions showed more hard tissue. Additionally, histograms of blue color in the malignant tended to be higher than the benign group. Conclusion: We suggested that quantitative ultrasound elastography and serum ferritin concentration comprise an alternative and non-invasive diagnostic method that could be used to predict the type of liver tumors in dogs. J. Adv. Vet. Anim. Res., 7(4): 575-584, Dec 2020 http://doi.org/10.5455/javar.2020.g455